Baylis-Hillman Reactions of Sulfonyl Aldimines or Aryl Aldehydes with 3-Methylpenta-3,4-dien-2-one or 3-Benzylpenta-3,4-dien-2-one - 施敏 郭英文 李红斌 (Chinese journal of chemistry, 2007)
The attempted Baylis-Hillman reactions of sulfonyl aldimines or aryl aldehydes with 3-methylpenta-3,4-dien-2-one or 3-benzylpenta-3,4-dien-2-one gave the corresponding Baylis-Hillman adducts in moderate yields in DMSO under the catalysis of DBU or PMe3, respectively. Moderate diastereoselectivities were observed in the reaction of 3-benzylpenta-3,4-dien-2-one with N-arylmethylidene-1-naphthalenesulfonamides catalyzed by chiral catalyst cinchona alkaloid derivative TQO {4-（3-ethyl-4-oxa-1-azatricyclo[4.4.0.0^3,8]dec-5-yl）quinolin-6-ol}.